PENDEKATAN MULTIKULTURAL DALAM PEMBELAJARAN BAHASA INGGRIS MELALUI MEDIA DONGENG PADA ANAK USIA DINI - Widhiya Ninsiana (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
Indonesia is a multicultural country, because it consists of various cultures, customs, and a variety of habits. These components are generally bonded together (integrated/embedded) with ethnicity, language, and culture. The use of foreign languages, especially English, in all its forms is related teaching foreign languages in formal and informal education in Indonesia. Even some foreign language has been introduced on early childhood. Seeing this phenomenon, educators must have a knowledge of foreign languages, willingness and skills to introduce and involve all educate into a global context. The introduction and engagement multicultural (cross-cultural disposition) that should be conducted transformative or practical experience (cross-cultural encounter) in learning English language, such as a fairytale. The multicultural approach in English learning by fairytale on early childhood will make the children more tolerant the other cultures.